Magnetic assessment and modelling of the Aramis undulator beamline. (6th April 2018) - Calvi, M.; Camenzuli, C.; Ganter, R.; Sammut, N.; Schmidt, Th.
Abstract : The design, the magnetic optimisation and the characterisation of the Aramis undulators are presented. The SUBLIME model integrates all the information gained during the series production and the test campaign to operate the Aramis undulator beamline, including phase matching and orbit correction. Abstract : Within the SwissFEL project at the Paul Scherrer Institute (PSI), the hard X‐ray line (Aramis) has been equipped with short‐period in‐vacuum undulators, known as the U15 series. The undulator design has been developed within the institute itself, while the prototyping and the series production have been implemented through a close collaboration with a Swiss industrial partner, Max Daetwyler AG, and several subcontractors. The magnetic measurement system has been built at PSI, together with all the data analysis tools. The Hall probe has been designed for PSI by the Swiss company SENIS. In this paper the general concepts of both the mechanical and the magnetic properties of the U15 series of undulators are presented. A description of the magnetic measurement equipment is given and the results of the magnetic measurement campaign are reported. Lastly, the data reduction methods and the associated models are presented and their actual implementation in the control system is detailed.